Effects of past and projected river discharge variability on freshwater production in an anadromous fish. (7th February 2018) - Ohlberger, Jan; Buehrens, Thomas W.; Brenkman, Samuel J.; Crain, Patrick; Quinn, Thomas P.; Hilborn, Ray
Abstract: Knowledge about population responses to environmental variability, including extreme climatic events, is crucial for understanding their current status and likely fate under future environmental change. The frequency and intensity of extreme events is projected to increase, especially in freshwater ecosystems. Anadromous fishes depend on freshwater habitats for spawning and juvenile rearing, making them sensitive to altered hydrologic regimes. Here, we evaluate the effect of past and projected variability in river hydrology on freshwater production of naturally spawning coho salmon populations from coastal river systems in Washington, USA. Using a stage‐based life‐cycle model, we show that juvenile production during freshwater residence depends on river flow characteristics. Most importantly, juvenile production is reduced by low minimum stream flows during summer. Based on climate model projections suggesting more extreme summer droughts in the region, we then simulate changes in river flow characteristics and quantify the effects of more frequent and severe low flows during summer on juvenile production as well as the harvest that can be sustained in these populations. Our results demonstrate that changes in hydrologic regimes due to environmental change, especially extreme low flows during summer, may significantly affect juvenile production in anadromous fishes such as coho salmon and the services these populations provide to their ecosystems and humans. Understanding population responses to extreme climatic events is thus essential for improving species conservation and risk assessments.